Caesarean delivery in a pregnant woman with epidermolysis bullosa: anaesthetic challenges. (May 2017) - Araújo, M.; Brás, R.; Frada, R.; Guedes-Martins, L.; Lemos, P.
Highlights: Epidermolysis bullosa is a rare disease. The presentation can be severe. The anaesthetic management of these patients is challenging. Labour management requires a multidisciplinary approach. Abstract: Epidermolysis bullosa is a heterogeneous group of hereditary diseases characterised by extreme fragility of skin and mucosa, with blister and lesion formation spontaneously or in response to trauma. Anaesthetic management of these patients is challenging with respect to positioning, monitoring, use of medical devices and airway management. These challenges are increased when managing labour. We report an elective caesarean delivery in a nulliparous woman with autosomal recessive dystrophic epidermolysis bullosa, managed successfully with spinal anaesthesia.